Gestión de inventario en la empresa electro partes de la cuidad de Babahoyo. - Coello Jiménez, Evelyn Ivette (2022)
The main objective of this case study called inventory management in the Electro Partes company in the city of Babahoyo is to evaluate the current state of inventory management within the Electro Parts company, this investigative work is related to the subline of investigation of companies and public and private institutions of the Commercial Engineering career of the Technical University of Babahoyo. Electro Partes is a company that constantly has problems related to the control and management of products, in addition to little knowledge of the administrative area, in this case study the interview research technique was used, the methodology was descriptive, in the that different bibliographic sources were used that support this investigative work. Inventory control is carried out manually, which has caused that on many occasions there is a lack of merchandise within the warehouses, in the most critical time of the COVID 19 pandemic, its profitability was not satisfactory, therefore it has not had growth in its capital, the company Electro Partes lacks adequate logistics, despite being an Ecuadorian entity, it has with suppliers from its own country reasons why it could not meet the needs of its customers, as a result of the fact that the import of products at the national was affected after the suspension of air flights. The company does not have a billing system that allows its customers to easily make the respective declarations to the SRI, Electro Partes does not have digital channels to be able to publicize its products.